2000
DOI: 10.1074/jbc.275.15.11425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Pals, Proteins Associated with mLin-7

Abstract: In Caenorhabditis elegans, three PDZ domain proteins, Lin-2, Lin-7, and Lin-10, are necessary for the proper targeting of the Let-23 growth factor receptor to the basolateral surface of epithelial cells. It has been demonstrated that homologues of Lin-2, Lin-7, and Lin-10 form a heterotrimeric complex in mammalian brain. Using Far Western overlay assay, we have identified additional proteins that can bind to the amino terminus of mLin-7 and cloned the genes encoding these proteins using bacterial expression cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
152
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 34 publications
(50 reference statements)
1
152
0
2
Order By: Relevance
“…Besides a PDZ domain, six additional protein-protein interaction domains have been identified in Nok and some of their targets have been identified in mammalian epithelial cell culture systems. Among these domains, the Nterminal conserved domain interacts with Par-6 (Hurd et al, 2003), L27N interacts with DLT (Roh et al, 2002), L27C interact with Lin7 (Kamberov et al, 2000). These proteins also likely interact with Nok in photoreceptors and assist in targeting Crumbs to the inner segments.…”
Section: Do Nok and Crb Mediate P-p Junctional Complexes As Another Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides a PDZ domain, six additional protein-protein interaction domains have been identified in Nok and some of their targets have been identified in mammalian epithelial cell culture systems. Among these domains, the Nterminal conserved domain interacts with Par-6 (Hurd et al, 2003), L27N interacts with DLT (Roh et al, 2002), L27C interact with Lin7 (Kamberov et al, 2000). These proteins also likely interact with Nok in photoreceptors and assist in targeting Crumbs to the inner segments.…”
Section: Do Nok and Crb Mediate P-p Junctional Complexes As Another Mmentioning
confidence: 99%
“…Such function of the nok gene has not been discovered before. The nok gene, zebrafish homolog of fly stardust and mouse pals1 (Hong et al, 2001;Kamberov et al, 2000), was initially identified for its function in retinal epithelial polarity and cellular pattern formation during early retinal development in zebrafish (Wei and Malicki, 2002). Our observation of Nok's continued expression in the junctional region between the inner segments of photoreceptors in fully developed retina promoted us to perform experiments to determine the function of Nok in photoreceptor adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2A depicts the domain structure of murine PALS1. The U1 region mutant V37G shows reduced binding with the polarity protein Par6 (Wang et al, 2004), the L27N domain mutant disrupts the interaction between PALS1 and PATJ (Roh et al, 2002), and the PALS1 L27C domain mutant does not bind Lin-7 (Kamberov et al, 2000). It has been shown that extensive intramolecular interactions exist between the C-terminal SH3 domain and the GUK domain of MAGUK proteins (McGee et al, 2001;Tavares et al, 2001).…”
Section: Wild-type Pals1 and Two Pals1 Mutants Rescue The Defects In mentioning
confidence: 99%
“…The PALS1-PATJ-CRB complex localizes to the tight junction of mammalian epithelial cells, and the disruption of the complex leads to defects in cell polarity (Straight et al, 2004). The C-terminal L27 (L27C) domain of PALS1 interacts with an L27 domain within Lin-7 (Kamberov et al, 2000), and prior work in our laboratory has shown that an evolutionarily conserved region in the N terminus of PALS1 mediates its interaction with Par6. This interaction links the polarity complexes PALS1-PATJ-CRB and Par3-Par6 -aPKC together (Hurd et al, 2003;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A second evolutionarily conserved protein complex, initially identified in epithelia of Drosophila, comprises the transmembrane protein Crumbs, which is linked by its C-terminal amino acids (ERLI) to the membrane-associated guanylate kinase (MAGUK) Stardust (Bachmann et al, 2001;Hong et al, 2001). Stardust recruits the scaffolding proteins DLin-7 and DPATJ into the complex (Kamberov et al, 2000;Roh et al, 2002;Bachmann et al, 2004). The proteins are localized in the subapical region, apical to the zonula adherens, a site that corresponds to that of tight junctions (which are not found in invertebrate epithelia) in vertebrate cells, and most of them are essential for the establishment and/or maintenance of epithelial polarity in the Drosophila embryo.…”
Section: Introductionmentioning
confidence: 99%